Hydrogel fibers for wearable sensors and soft actuators - Jiaxuan Du; Qing Ma; Binghao Wang; Litao Sun; Limei Liu (iScience, 2023)
Summary: Owing to superior softness, wetness, responsiveness, and biocompatibility, bulk hydrogels are being intensively investigated for versatile functions in devices and machines including sensors, actuators, optics, and coatings. The one-dimensional (1D) hydrogel fibers possess the metrics from both the hydrogel materials and structural topology, endowing them with extraordinary mechanical, sensing, breathable and weavable properties. As no comprehensive review has been reported for this nascent field, this article aims to provide an overview of hydrogel fibers for soft electronics and actuators. We first introduce the basic properties and measurement methods of hydrogel fibers, including mechanical, electrical, adhesive, and biocompatible properties. Then, typical manufacturing methods for 1D hydrogel fibers and fibrous films are discussed. Next, the recent progress of wearable sensors (e.g., strain, temperature, pH, and humidity) and actuators made from hydrogel fibers is discussed. We conclude with future perspectives on next-generation hydrogel fibers and the remaining challenges. The development of hydrogel fibers will not only provide an unparalleled one-dimensional characteristic, but also translate fundamental understanding of hydrogels into new application boundaries.